Effect of L-Citrulline on Creatine Kinase MM (CK-MM) Isoenzymes in Mice: An In Vivo Study Focusing on Immunohistochemistry Analysis - Ghozali, Dhoni Akbar; Rahma, Annisa Aghnia; Hanifa, Shafira Nur; Ilyas, Muhana Fawwazy (Folia Medica Indonesiana, 2024)
Highlights: 1. This study elucidates the effect of L-citrulline supplementation on creatine kinase MM (CK-MM) expression post-eccentric exercise, offering novel insights into its potential role in mitigating muscle damage. 2. The findings demonstrate that L-citrulline administration significantly reduces CK-MM expression levels in skeletal muscle tissue, suggesting its therapeutic potential in enhancing muscle recovery and performance following exercise-induced damage. 3. This study contributes valuable insights into the multifaceted benefits of L-citrulline supplementation for supporting overall muscle health and performance by identifying its protective effects under different mechanisms, including improved blood flow, antioxidant activity, enhanced mitochondrial function, and promotion of muscle protein synthesis. Abstract Eccentric exercise often induces muscle injuries in athletes, resulting in impaired performance and prolonged recovery time. Creatine kinase MM (CK-MM) is a biomarker for assessing muscle damage, with elevated levels indicating injury. L-citrulline, an amino acid, has shown promise in enhancing performance and reducing recovery time. However, its specific effect on CK-MM remains unclear. This study utilized immunohistochemistry analysis to investigate the effect of L-citrulline supplementation on CK-MM expression post-eccentric exercise in male BALB/c mice. This in vivo study was conducted with a post-test-only design. A total of 25 mice were divided into two control groups (normal/C1 and negative/C2) and three treatment groups (T1, T2, and T3), each containing five mice. The T1, T2, and T3 groups were daily administered 250, 500, and 1,000 mg/kg bw of L-citrulline for seven days, respectively. All mice, except the C1 group, performed a downhill running procedure. The CK-MM expression in skeletal muscle tissue post-eccentric exercise was assessed using immunohistochemistry analysis. The statistical analysis included the Shapiro-Wilk test for data distribution and the Kruskal-Wallis and Mann-Whitney post-hoc tests for significant differences (p<0.05). The results showed that CK-MM expression in the C2 group (91.00±2.24%) was significantly higher (p=0.008) than that of the C1 group (70.00±10.0%). Subsequently, the T1 (68.00±9.08%, p=0.008), T2 (72.00±7.58%, p=0.008), and T3 (67.00±9.75%, p=0.008) groups exhibited significantly lower expressions than the C2 group. These results were consistent with the role of CK-MM as a marker for muscle damage, and they indicated that L-citrulline might have a protective effect against muscle damage post-eccentric exercise. However, no significant differences were observed among the C1, T1, T2, and T3 groups. In conclusion, L-citrulline supplementation demonstrates promise in attenuating muscle damage following eccentric exercise, as evidenced by reduced CK-MM expression levels. These findings highlight the potential therapeutic role of L-citrulline in enhancing muscle recovery and performance.